Proteínas relacionadas con el metabolismo del hierro corporal (2016)
ABSTRACT: Iron is an essential nutrient well studied for its role in human health, and much evidence exists regarding its metabolism, functions, interactions, and regulations. However, studies and analyses that have been done are often based on specific proteins and few integrate into a single text the characteristics of multiple proteins related to total body iron metabolism. Objective: Explore in-depth the molecular, metabolic, and modulation aspects of proteins that participate in iron homeostasis and related interactions. Materials and methods: A literature review was completed using scientific databases in conjunction with a search for related scientific articles published between 2006 and 2016. Results: Homeostasis of total body iron stores is a complex process that is highly regulated by various molecules that participate in an integrated manner in iron metabolism. In recent years, new proteins have been discovered regarding the humoral and cellular control of iron, some of which are also involved in the transport of other nutrients. Additionally, these proteins involve participation from various organs, tissues, and systems. This review includes proteins responsible for facilitating biological utilization of the nutrient, as well as those that protect cells from toxicity of this mineral.